Carotenoids Content and Antioxidant Capacity of Underutilized Tropical Fruits - Khoo, Hock Eng (2009)
This study was conducted to evaluate the total carotene content (TCC), β-carotene, antioxidant capacity and stability study of 12 Malaysian underutilized fruits. TCC and β-carotene content were determined using UV-Vis spectrophotometric and HPLC methods, respectively; while antioxidant capacity was determined using DPPH, FRAP and haemoglobin oxidation assays. TCC of the studied fruits was ranged from 1.4–19.8 mg/100 g edible portions. Jentik-Jentik had the highest β-carotene content followed by Cerapu 2, Durian Nyekak 2, Tampoi Kuning, Durian Nyekak 1 and Cerapu 1. TCC of the underutilized fruits was in the order of Jentik-Jentik > Durian Nyekak 2 > Durian Nyekak 1 > Cerapu 2 > Cerapu 1 > Tampoi Kuning > Bacang 1 > Kuini > Bacang 2 > Durian Daun > Bacang 3 > Tampoi Putih. Results of DPPH and FRAP assays showed that Cerapu had the highest antioxidant capacity, while Tampoi Kuning had the lowest capacity compared to other studied fruits. Cerapu had EC50 of 219.5 mg/L, while other fruits had no EC50. For haemoglobin oxidation assay, the studied fruit extracts at higher concentration were able to significantly reduce the production of hydrogen peroxide induced malondialdehyde (MDA) compared to the control. A significant reduction in MDA level of red blood cell (RBC) was found after treated with Durian Nyekak 2 and commercial mango (control) extracts. In stability study, the degradation of TCC in Bacang 1, Bacang 3, Kuini and Tampoi Putih was more than 30% at day 12th of storage at −20°C. However, less than 5% degradation was observed in Cerapu 1 and Cerapu 2. For Cerapu 2, Durian Nyekak 2 and Jentik-Jentik, there were less than 15% of TCC of the studied samples degraded during storage at 0°C for 5 h. A rapid degradation of carotenoids occurred when the studied samples were stored at 0°C than −20°C. The study indicated that among the studied fruits, Jentik-Jentik and Cerapu had the highest carotene content and antioxidant capacity, respectively. Moreover, Cerapu extract had the slowest TCC degradation rate for the studied storage time and temperature.